2012
DOI: 10.1007/bf03262199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol in Paclitaxel Injections on the Ethanol Concentration in Exhaled Breath

Abstract: Background: Ethanol is included in certain injectable preparations of anticancer drugs to increase their solubility. Since the volume of ethanol in these preparations is approximately half of the total injection volume, the potential inhibitory effects of ethanol on the central nervous system cannot be disregarded, especially considering that patients may drive immediately after administration of the medication. Therefore, the concentration of ethanol was examined in exhaled breath after administration of pacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…18 Of the three studies that evaluated the presence of ethanol in expired air, only one detected the substance. 22 No ethanol was detected in saliva—even at the end of docetaxel infusion. Finally, low plasma ethanol concentrations were measured after 3 hours of paclitaxel infusions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…18 Of the three studies that evaluated the presence of ethanol in expired air, only one detected the substance. 22 No ethanol was detected in saliva—even at the end of docetaxel infusion. Finally, low plasma ethanol concentrations were measured after 3 hours of paclitaxel infusions.…”
Section: Resultsmentioning
confidence: 99%
“…Seven articles analyzed the occurrence of ethanol-related symptoms and/or the detectability of ethanol in expired air, saliva, or blood plasma. 8,12,13,17,18,21,22 A retrospective comparison of five docetaxel formulations showed that the safety profile was worse when the dose of both excipients (ethanol and polysorbate) was high—notably with regard to injection site reactions ( P = .0012), hand-foot syndrome ( P = .0003), and oral mucositis ( P = .008). 13 Another study evaluated paclitaxel infusions in 25 patients with a polymorphism in the gene coding for type 2 aldehyde dehydrogenase ( ALDH2 ): five patients developed grade 1 ethanol-related adverse events.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations